Impaired recognition of interactive intentions in adults with autism spectrum disorder not attributable to differences in visual attention or coordination via eye contact and joint attention - Jording, Mathis; Hartz, Arne; Vogel, David H. V.; Schulte-Rüther, Martin; Vogeley, Kai (Scientific reports, 2024)
Altered nonverbal communication patterns especially with regard to gaze interactions are commonly reported for persons with autism spectrum disorder (ASD). In this study we investigate and differentiate for the first time the interplay of attention allocation, the establishment of shared focus (eye contact and joint attention) and the recognition of intentions in gaze interactions in adults with ASD compared to control persons. Participants interacted via gaze with a virtual character (VC), who they believed was controlled by another person. Participants were instructed to ascertain whether their partner was trying to interact with them. In fact, the VC was fully algorithm-controlled and showed either interactive or non-interactive gaze behavior. Participants with ASD were specifically impaired in ascertaining whether their partner was trying to interact with them or not as compared to participants without ASD whereas neither the allocation of attention nor the ability to establish a shared focus were affected. Thus, perception and production of gaze cues seem preserved while the evaluation of gaze cues appeared to be impaired. An additional exploratory analysis suggests that especially the interpretation of contingencies between the interactants’ actions are altered in ASD and should be investigated more closely.